Perencanaan Persediaan Produk Steering Handle Sepeda Motor Pada UD. Aji Batara Perkasa Dengan Menggunakan Metode ABC - Iman Syah Alif Ahmadi; Setijanen Djoko Harijanto (Lembaga Pengembangan Kinerja Dosen, 2023)
UD. Aji Batara Perkasa is a company engaged in the manufacturing sector that produces various Motor Spare Parts, UD. Aji Batara Perkasa is located on Jl. Colonel Sugiono No. 175B, Pulosari, Kureksari, Kec. Waru, Sidoarjo Regency, East Java, 61256. UD. So far Aji Batara Perkasa has not applied the ABC method in classifying the use of raw materials, grouping goods in the ABC method based on the total sales value in a year. The purpose of this research is to find out what types of raw materials are included in groups A, B, and C With the ABC method, it can be seen that the raw materials with the highest, medium and lowest investment and the turnover of these raw materials are based on their use.